Studi Literatur Kejahatan Siber Pada Sistem Perbankan Syariah Di Era 4.0 - Khairrun Nisa; Chairina Chairina (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2022)
Electronic technology is growing at the same rate as the number of crimes, from the traditional to those using expertise in electronic technology for their own benefit or that of others. This study aims to determine whether the rapid development of technology has caused negative excesses, including the growth of a more sophisticated type of crime known as cybercrime and the use of sophisticated information technology and computers by criminals in banking for the purpose of stealing card data and customer money. The author analyzed previous research using a literature review approach in this study. Various Islamic banking crimes in Indonesia can be learned from the findings of this study.